Feasibility and efficacy of a novel audiovisual tool to increase colorectal cancer screening among rural Appalachian Kentucky adults - Kruse-Diehr, Aaron J.; Cegelka, Derek; Holtsclaw, Elizabeth; Edward, Jean S.; Vos, Sarah C.; Karrer, Melissa; Bathje, Katie; Rogers, Melinda; Russell, Elaine; Knight, Jennifer Redmond (Frontiers in Public Health, 2024)
Introduction: Residents of Appalachian regions in Kentucky experience increased colorectal cancer (CRC) incidence and mortality. While population-based screening methods, such as fecal immunochemical tests (FITs), can reduce many screening barriers, written instructions to complete FIT can be challenging for some individuals. We developed a novel audiovisual tool ("talking card") to educate and motivate accurate FIT completion and assessed its feasibility, acceptability, and effectivenessefficacy. Materials and Methods: We collected data on the talking card via: (1) cross-sectional surveys exploring perceptions of images, messaging, and perceived utility; (2) follow-up focus groups centered on feasibility and acceptability; and (3) effectiveness efficacy testing in communitybased FIT distribution events, where we assessed FIT completion rate, number of positive vs. negative screens, demographic characteristics of participants, and primary drivers of FIT completion.Results: Across the three study phases, 692 individuals participated. Survey respondents positively identified with the card's sounds and images, found it highly acceptable, and reported high-to-very high self-efficacy and response efficacy for completing FIT, with nearly half noting greater likelihood to complete screening after using the tool. Focus group participants confirmed the acceptability of the individuals featured on the card. Nearly 75% of participants provided a FIT accurately completed it, with most indicating the talking card, either alone or combined with another strategy, helped with completion. Discussion: To reduce CRC screening disparities among Appalachian Kentuckians, populationbased screening using contextually relevant implementation strategies must be used alongside clinic-based education. The talking card represents a novel and promising strategy to promote screening uptake in both clinical and community settings.